2016
DOI: 10.1007/s11682-016-9550-5
|View full text |Cite
|
Sign up to set email alerts
|

Multi-parametric quantitative MRI of normal appearing white matter in multiple sclerosis, and the effect of disease activity on T2

Abstract: White matter (WM) lesions with a distinct lesion-tissue contrast are the main radiological hallmark of multiple sclerosis (MS) in standard magnetic resonance imaging (MRI). Pathological WM changes beyond lesion development lack suitable contrasts, rendering the investigation of normal appearing WM (NAWM) more challenging. In this study, repeat quantitative MRI (qMRI) was collected in 9 relapsing remitting MS patients with mild disease over nine months. The relaxation times T1 and T2, the proton density (PD), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 42 publications
2
38
1
1
Order By: Relevance
“…These patients were scored on the Expanded Disability Status Scale (EDSS) before the first scan . The patient pool comprised participants who had previously been included in cross‐sectional analyses, and we also used data obtained from a previous study into white matter …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…These patients were scored on the Expanded Disability Status Scale (EDSS) before the first scan . The patient pool comprised participants who had previously been included in cross‐sectional analyses, and we also used data obtained from a previous study into white matter …”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown the value of qMRI for assessing tissue damage in MS: A study into WM pathology has demonstrated changes in tissue parameters in accordance with inflammatory activity . In the cortex, a region of interest (ROI) analysis showed that cortical T 1 prolongation and PD increase are present in early MS, indicating cortical damage .…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…MR imaging, particularly using multiparametric quantitative techniques (T 1 , T 2 and T 2 * relaxation time measurements, diffusion and magnetization transfer ratio measurements), and MR spectroscopy have been widely used to explain the disease's physiopathology mechanisms including those of observed in the normal appearing white matter (Reitz et al, 2016). In recent years, NMR or mass spectrometry metabolomics, has been used to investigate the metabolite changes in only cerebrospinal fluid which reflects the tissue inflammation associated with EAE (Smolinska et al, 2011;Blanchet et al, 2011;Smolinska et al, 2012;Noga et al, 2012;Lutz et al, 2013;Gebregiworgis et al, 2013;Mangalam et al, 2013;Coulier et al, 2013;Cocco et al, 2015;Dickens et al, 2015;Poisson et al, 2015) or MS (Sinclair et al, 2010;Lutz et al, 2007;Villostada et al, 2017;Bhargava and Calabresi, 2016;Pieragostino et al, 2015;Dickens et al, 2014;Reinke et al, 2014;Vingara et al, 2013;Moussalieh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%